Didactic, Linguistic and Intercultural Benefits of Mutual Teaching Placements in the UK and Austria (Pedagogical Horizons, 2017)
The present article is the first in a series revolving around mutual international teaching placements, lasting between 2 to 4 weeks, which the Private University of Education, Diocese of Linz, Austria (Private Pädagogische Hochschule der Diözese Linz, PHDL) have been organising and running with our partners and affiliated schools in the UK (York/Edinburgh) and Austria (Linz/Bad Goisern) since 2007. The project, per se, can be considered a highly successful immersion programme for primary and secondary trainees alike, benefitting them not only in terms of their teaching capacity (methodology/didactics), but also as regards their second language proficiency and cross-cultural awareness. After a short outline of the history of the project, some light will be cast on the practicalities and workload involved, which is usually minimal for Austrian schools, but can be quite considerable for UK schools. Finally, in order to round matters off, the concept of the project’s questionnaire design will be briefly introduced, which aims to place the project on a sound academic footing (research), evaluating the participants’ experiences from a wide range of different perspectives (cross-cultural studies, linguistics, didactics and methodology, school systems).
Keywords: international teaching placements; language proficiency; intercultural awareness; didactics and methodology; education systems; teaching styles